HUBUNGAN GAYA KEPEMIMPINAN KEPALA PAUD DENGAN KINERJA GURU DI KECAMATAN SEMENDAWAI BARAT - Claria Dara Mania; Mardeli Mardeli; Lidia Lidia (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2022)
This research is entitled “the relationship between early childhood leadership style and teacher performance in the district Semendawai Barat” This type of research is quantitative using the correlational method, namely looking at the relationship between the variabel X and variabel Y. the sampel used in this study were 15 payd institutions in the district Semendawai Barat. As for the way of collecting data that is using a questionnaire and documentation. In this study, the researcher used the guttman scale, which is a scale that uses only two choices, namely yes or no. if the respondent answers incorrectly, wil get a value of 1, but if respondent answer incorrectly, get a value of 0. Before conducting the research, the researcher conducted a trial sample first, namely the Cempaka district with 12 early childhood institutions. Aftergetting the vtest results, the next research tested the data using validity and reliability tests. Ater that the research into the actual sampel, namely early childhood institutions in the district of Semendawai Barat. Data analysis used is normality test, linier test, and hypothesis testing. The results obtained from the correlation coefficient value > that is 4,30753 > 2,080 which means Ho is rejected and Ha is accepted. It can be concluded that there is a significant relationship between variable X and variable Y. As for the results of the relationship between variable X and variable Y, namely 0,469 so that the relationship between variable X and variable Y is equal to.